2022
DOI: 10.1109/tsg.2022.3147370
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Robust Model Predictive Control-Based Energy Management Strategy for Islanded Multi-Microgrids Considering Uncertainty

Abstract: A microgrid is considered to be a smart power system that can integrate local renewable energy effectively. However, the intermittent nature of renewable energy causes operating pressure and additional expense in maintaining the stable operation by the energy management system in a microgrid. The structure of multimicrogrids provides the possibility to construct flexible and various energy trading framework. In this paper, in order to reduce the adverse effects of uncertain renewable energy output, a distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(21 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…MMGs have the prospect in resource coordination in a medium range, satisfy more energy demand, and avoid the high cost of interconnection construction with utility grid. Zhao et al [12] introduced an energy management strategy of MMG based on distributed robust model predictive control to deal with the uncertainty of DER. The daily operating cost of each MG with the proposed strategy has been reduced by 5.3%, 8.9%, and 6.9% compared with the independent operation.…”
Section: Introductionmentioning
confidence: 99%
“…MMGs have the prospect in resource coordination in a medium range, satisfy more energy demand, and avoid the high cost of interconnection construction with utility grid. Zhao et al [12] introduced an energy management strategy of MMG based on distributed robust model predictive control to deal with the uncertainty of DER. The daily operating cost of each MG with the proposed strategy has been reduced by 5.3%, 8.9%, and 6.9% compared with the independent operation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the energy management based on imperfect prediction information should provide necessary robust capacity to amend the supply-demand imbalance caused by prediction error. A distributed robust model predictive control -based energy management strategy is proposed in [5] for islanded multi-microgrids in order to reduce the adverse effects of uncertain renewable energy output. In our prior work [6], we proposed an adaptive distributed power scheduling algorithm for renewable microgrid cooperation.…”
Section: Introductionmentioning
confidence: 99%
“…Although this EMS optimised the energy cost for each microgrid and reduced the computational power needed, the robustness to prediction uncertainty and the effect of communication loss was not studied. The best optimisation and robustness results reported in the literature have been achieved using model predictive control (MPC) 4,6,8,9,20‐22 . This is because the prediction uncertainty inherent in renewable energy supplies can be included in the optimiser.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in 28‐30 the available generation (solar and wind) has been modelled using probability distributions, while in 24 the authors reported that probability density functions are used as a general trend to characterise the uncertainty of the prediction models. In 22 a robust MPC strategy for a multi‐microgrid system was presented. The strategy optimised the energy sold by each microgrid while ensuring their own power consumption in each local microgrid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation